2018
DOI: 10.3390/cli6020033
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Univariate and Joint Bias Correction Methods in Changing Climate From a Hydrological Perspective

Abstract: Abstract:In this paper, the ability of two joint bias correction algorithms to adjust biases in daily mean temperature and precipitation is compared against two univariate quantile mapping methods when constructing projections from years 1981-2010 to early (2011-2040) and late (2061-2090) 21st century periods. Using both climate model simulations and the corresponding hydrological model simulations as proxies for the future in a pseudo-reality framework, these methods are inter-compared in a cross-validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
(70 reference statements)
0
42
0
Order By: Relevance
“…Chen et al (2018) found that the joint bias correction of precipitation and air temperature led to a much better performance in terms of hydrological modelling for all their study basins located in various climates except for the coldest Canadian basin. In contrast, an overall additional benefit of using bivariate bias correction methods for hydrological impact projections was not evident in results by 15 Räty et al (2018) when compared to using a univariate quantile mapping applied as a delta change method, i.e. retaining present-day correlation structures.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Chen et al (2018) found that the joint bias correction of precipitation and air temperature led to a much better performance in terms of hydrological modelling for all their study basins located in various climates except for the coldest Canadian basin. In contrast, an overall additional benefit of using bivariate bias correction methods for hydrological impact projections was not evident in results by 15 Räty et al (2018) when compared to using a univariate quantile mapping applied as a delta change method, i.e. retaining present-day correlation structures.…”
Section: Discussionmentioning
confidence: 88%
“…An advantage of using a bivariate bias correction approach was not evident for the coldest snow- dominated catchment of the sample though. According to Räty et al (2018) their hydrological simulations did not substantially benefit from bivariate bias correction approaches, whereas simulations of high flows and snow water equivalents in snow-influenced catchments improved slightly in comparison to simulations using univariate-corrected climate model data.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, dOTC proposes a definition of nonstationarity, and explicitly gives what the correction corresponds to (the evolution of the model applied to observations). In the particular case of the temperatures/precipitation correction, compared to, e.g., Piani and Haerter (2012) and Räty et al (2018), the correction is at least as good during the calibration period, although the comparison is not done over the projection period, because the indicators are different.…”
Section: Discussionmentioning
confidence: 99%
“…To make an initial assessment, one multivariate method is chosen to be combined with the different occurrence-bias-adjusting techniques, namely the Multivariate Bias Correction in n dimensions (MBCn) method (Cannon, 2018). This method is chosen 75 as it is one of the more commonly implemented multivariate bias-adjusting methods (Räty et al, 2018;Meyer et al, 2019;Zscheischler et al, 2019). Additionally, it only differs from the QDM method in the final step, where a rank-based shuffling is applied.…”
Section: Introductionmentioning
confidence: 99%